Effect of levothyroxine treatment on fetal growth among women with mild subclinical hypothyroidism and thyroid peroxidase antibody negative: a cohort study - Yuelong Ji; Jinhui Xu; Tao Su; Lizi Lin; Shuang Zhou; Heling Bao; Zheng Liu; Shusheng Luo; Xiangrong Xu; Na Han; Hai-Jun Wang (BMC, 2023)
Abstract Background Some clinicians used levothyroxine (LT4) treatment for mild subclinical hypothyroidism (SCH) pregnant women (2.5 < thyroid-stimulating hormone (TSH) ≤ the pregnancy-specific reference range with normal free thyroxine (FT4) level) with thyroid peroxidase antibody negative (TPOAb−), although the recent clinical guideline did not recommend it. It is unknown whether LT4 treatment for pregnant women with mild SCH and TPOAb− have impact on fetal growth. Therefore, the aim of the study was to investigate the effect of LT4 treatment on fetal growth and birth weight among mild SCH pregnant women with TPOAb−. Methods This was a birth cohort study including 14,609 pregnant women between 2016 and 2019 in Tongzhou Maternal and Child Health Hospital of Beijing, China. Pregnant women were divided into 3 groups as follows: Euthyroid (n = 14,285, 0.03 ≤ TSH ≤ 2.5mIU/L, normal FT4), TPOAb−; Untreated mild SCH with TPOAb− (n = 248, 2.5 < TSH ≤ 2.9mIU/L, normal FT4, without LT4 treatment); Treated mild SCH with TPOAb− (n = 76, 2.5 < TSH ≤ 2.9mIU/L, normal FT4, with LT4 treatment). The main outcome measures were Z-scores of fetal growth indicators (abdominal circumference (AC), biparietal diameter (BPD), femur length (FL), head circumference (HC), estimated fetal weight (EFW)), fetal growth restriction (FGR) and birth weight. Results There was no difference in fetal growth indicators and birth weight between the untreated mild SCH women with TPOAb− and the euthyroid pregnant women. But the HC Z-score was lower in the LT4 treated mild SCH women with TPOAb−, compared with the euthyroid pregnant women (β = -0.223, 95%CI: -0.422, -0.023). The LT4 treated mild SCH women with TPOAb− had lower fetal HC Z-score (β = -0.236, 95%CI: -0.457, -0.015), compared with the untreated mild SCH women with TPOAb−. Conclusions We observed that LT4 treatment for mild SCH with TPOAb− was associated with decreased fetal HC, which was not observed for untreated mild SCH women with TPOAb−. The adverse effect of LT4 treatment for mild SCH with TPOAb− provided new evidence for the recent clinical guideline.